Muhammad Boudaoud and his activity in the field of armaments during the liberation revolution - bin Hamouda, Murad (The Algerian Historical Journal, 2026)
The personality of Mohamed Boudaoud, called "Si Mansour", is considered as one of the prominent personalities who were active in the field of armaments during the revolution. However, this personality did not receive sufficient attention, although he is considered as one of the first to go to the western side on a mission to bring weapons. Strong with Algerians residing in Morocco or with Moroccans, These relationships enabled him to succeed in arms smuggling operations, as he worked at first with Mohamed Boudiaf and then under the leadership of Abd el hafid Bousouf, who became one of his loyal men. Firstly, His activity focused on the western side in the operations of passing weapons to the goal of the Algerian borders. Then, his activity expanded to include his supervision of the weapons industry workshops, where the workshop he supervised was able to manufacture a lot of weapons that the army benefited from until achieving independence.